Service quality in education: Management students' perspective - Jusoh, Ahmad; Omain, Siti Zaleha; Abdul Majid, Norazman; Shamsuddin, Ahmad Sharifuddin; Md Som, Hishamudin (2004)
According to some scholars, the strategic success of a service organization depends on its ability to consistently meet or exceed customer service expectations. This study thus set out measure the service quality performance of a faculty in a public university. Based on stratified random sampling on 229 students employing a survey instruments that measure six dimensions of quality attributes, the result of the study revealed that the level of service quality in this particular faculty is moderate. Analysis showed that there are significant differences based on the students’ perception of this faculty service quality by year of study and race. However, there are no significant differences based on gender. Implication and limitation of the study are highlighted and further research discussions are suggested.